Patterns of sexual dimorphism in Mexican alligator lizards, Barisia imbricata - Dashevsky, Daniel (Blackwell Publishing Ltd, 2013)
We compare morphological characteristics of male and female Barisia imbricata, Mexican alligator lizards, and find that mass, head length, coloration, incidence of scars from conspecifics, tail loss, and frequency of bearing the color/pattern of the opposite sex are all sexually dimorphic traits. Overall size (measured as snout–vent length), on the other hand, is not different between the two sexes. We use data on bite scar frequency and fecundity to evaluate competing hypotheses regarding the selective forces driving these patterns. We contend that sexual selection, acting through male-male competition, may favor larger mass and head size in males, whereas large females are likely favored by natural selection for greater fecundity. In addition, the frequency of opposite-sex patterning in males versus females may indicate that the costs of agonistic interactions among males are severe enough to allow for an alternative mating strategy. Finally, we discuss how sexual and natural selective forces may interact to drive or mask the evolution of sexually dimorphic traits.